Beautiful economic features of public landscaping in city beautiful - Emilson Caputo Delfino Silva; Adriana Marasca (Ornamental Horticulture, 2013)
City beautiful was a movement of great reach and inspiration, which apparently, was initiated in Chicago in 1893 during the World’s Columbian Exposition. The movement’s premises were artistic, architectural, social, political and economic. Among the artistic and architectural aspects of the city beautiful movement, the provision of high quality public landscaping was of paramount importance. As for the economic rationale behind the movement, we encounter the thinking that a beautiful city should increase its residents’ enjoyment of the city’s attributes and hence attachment to the city, raise real estate values as well as expand city business, with larger sales of city goods and services to local and touristic customers. This paper examines the economic rationale behind the city beautiful movement. We consider a “regional” economy consisting of two adjacent cities, which are identical in many of its attributes, such as the sizes of their populations. We build a general equilibrium model for the agents (consumers and producers) in this economy and demonstrate that the economic rationale behind the city beautiful movement is sound. Each city’s wealth and welfare are proportional to its quality level and a city’s quality level is proportional to the city’s public landscaping quality.